PARTISIPASI MASYARAKAT DALAM PROGRAM PERCEPATAN PENURUNAN STUNTING “SOTH” DI KOTA SURABAYA - Tria Anggraini; Tukiman (Journal Publicuho, 2025)
This program aims to provide parents with education on appropriate child care models and balanced family nutrition. This study uses a descriptive qualitative approach to identify and describe the role of the community in efforts to reduce the prevalence of stunting in Nginden Jangkungan Village, Surabaya City. The data collection process was carried out through observation, in-depth interviews, documentation and focus group discussions with the Nginden Jangkungan Village Chief, Surabaya Hebat Cadre Chief, Nginden Jangkungan Village, Sekolah Orang Tua Hebat RW03 Chief, Nginden Jangkungan Village and the community or participants in the Sekolah Orang Tua Hebat program. The results of the study showed that the Nginden Jangkungan village community was actively involved in the implementation of this program. However, the aim of this program should include the role of fathers in the meetings, for example, by forming a Father Gerat class and providing further assistance to implement the guidelines or actual practices aimed at bringing the community closer together.